Formalizing Lacanian psychoanalysis through the free energy principle - Li, Lingyu; Li, Chunbo (Frontiers in Psychology, 2025)
This study presents a computational formalization of Lacanian psychoanalysis using the framework of the free energy principle (FEP)—a theoretical framework for modeling self-organizing systems across multiple scales. We first examine the theoretical compatibility between the two frameworks, highlighting their shared (1) Kantian epistemological foundations regarding the unknowability of reality, (2) constructive nature of internal representational systems, (3) non-linear temporal dynamics that combine prediction and retrospection, and (4) emphasis on representation failures as key driving forces. Building on these convergences, we develop a computational framework that implements core Lacanian concepts through the FEP framework. Through multi-level simulations, this framework captures the interdependence of three orders as a message-passing network, formalizes desire as generalized synchronization between subjects' Symbolic orders, and models the Other through collective dynamics. This FEP-based reformulation renders traditionally obscure Lacanian concepts computationally tractable, thereby establishing a conceptual bridge between Lacanian psychoanalytic insights and cognitive science.